EVALUASI PELAKSANAAN PENYEDIAAN INFRASTRUKTUR PERMUKIMAN PADA PROGRAM KOTAKU DI KELURAHAN PANCOR KABUPATEN LOMBOK TIMUR - NOVIA ARIANA; I DEWA MADE ALIT KARYAWAN (Universitas Mahasaraswati K. Mataram, 2023)
The importance of handling slum settlements is one of the tasks faced by the Central, Provincial, and Regency Governments to create livable settlements through the Cities Without Slums/ Kota Tanpa Kumuh (KOTAKU) Program. The KOTAKU program is a community-based program, to carry out infrastructure activities such as physical, economic, and social improvement and development. The success of the program needs to be monitored for compliance with what is planned. Because of this, it is necessary to evaluate the implementation of settlement infrastructure provision in the KOTAKU program. The analysis is based on a quantitative approach through literature studies from previous studies. Supporting data was obtained from institutions related to the KOTAKU program in Pancor Village, Selong City, East Lombok Regency. The success of the program is shown by changes in the behavior of people's lives and the quality of the environment so that the handling of slum settlements is achieved